Security of medical images for telemedicine: a systematic review - Magdy, Mahmoud; Hosny, Khalid M.; Ghali, Neveen I.; Ghoniemy, Said (Multimedia tools and applications, 2022)
Recently, there has been a rapid growth in the utilization of medical images in telemedicine applications. The authors in this paper presented a detailed discussion of different types of medical images and the attacks that may affect medical image transmission. This survey paper summarizes existing medical data security approaches and the different challenges associated with them. An in-depth overview of security techniques, such as cryptography, steganography, and watermarking are introduced with a full survey of recent research. The objective of the paper is to summarize and assess the different algorithms of each approach based on different parameters such as PSNR, MSE, BER, and NC.